2003
DOI: 10.1002/bem.10132
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 10 kV, 30 μT, 60 Hz electric and magnetic fields on milk production and feed intake in nonpregnant dairy cattle

Abstract: Milk production is the main agricultural income in the province of Québec, and the electrical distribution network traverses the rural dairy production region. This study evaluates the hypothesis that electric and magnetic fields may affect dairy production. Sixteen multiparous nonpregnant lactating Holstein cows (weighing 662 +/- 65 kg and with 150.4 +/- 40 days of lactation) were confined to wooden metabolic crates during the experiment with a 12:12 h light:dark cycle. The cows were divided into two replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
2
2
0
Order By: Relevance
“…The results obtained for dry matter intake (DMI), protein and energy intake, are in agreement with the expected intake according to the nutritional requirements for dairy cattle of the National Research Council [NRC, 1989]. The variations in DMI, P4, MLT, PRL, and IGF-1 associated with EMF exposure observed in previous experiments [Burchard et al, 1996[Burchard et al, , 1998a[Burchard et al, ,b, 1999[Burchard et al, , 2003Rodriguez et al, 1998], were not detected in this experiment.…”
Section: Resultssupporting
confidence: 89%
“…The results obtained for dry matter intake (DMI), protein and energy intake, are in agreement with the expected intake according to the nutritional requirements for dairy cattle of the National Research Council [NRC, 1989]. The variations in DMI, P4, MLT, PRL, and IGF-1 associated with EMF exposure observed in previous experiments [Burchard et al, 1996[Burchard et al, , 1998a[Burchard et al, ,b, 1999[Burchard et al, , 2003Rodriguez et al, 1998], were not detected in this experiment.…”
Section: Resultssupporting
confidence: 89%
“…After installing the shielded neutral isolation transformer, cows stopped dancing and milk production gradually recovered to its highest previous level after about 18 months [ 59 ]. Similar studies have confirmed that exposure (10 kV m −1 , 30 μT, 60 Hz) resulted in moderate (5%) decreases in both milk yield and milk fat percentage as well as an increase in dry matter intake in non-lactating non-pregnant dairy cows [ 60 ].…”
Section: Resultssupporting
confidence: 54%
“…The fact that the effect of MF was not uniform during different weeks, evidenced by the treatment by week interaction, might contribute to explain this MF effect on body weight and weekly body weight gain. Simultaneous application of EF and MF increased DMI [Burchard et al, 1996;Rodriguez et al, 2002;Burchard et al, 2003] and weight gain [Rodriguez et al, 2002] in dairy cattle. Conversely, exposure to 10 kV/m EFs does not affect DMI in dairy heifers .…”
Section: Discussionmentioning
confidence: 99%